STUDI STARTING DAN RESISTANSI STATOR TERHADAP SLIP, ARUS AWAL, DAN KUALITAS DAYA MOTOR INDUKSI - Irenius Aditya Lumbangaol; Andira; Muhammad Ikbal; Desman Jonto Sinaga; Arwadi Sinuraya (JURNAL ILMIAH NUSANTARA, 2026)
This study presents a literature review on the influence of starting methods and stator resistance on slip characteristics, inrush current, and power quality performance of three-phase induction motors. Several starting strategies including direct-on-line (DOL), star–delta, autotransformer, soft-starter, and voltage–frequency (V/f) control using inverter-based drives are reviewed to evaluate their effect on initial current surge and electromagnetic torque development. Findings indicate that conventional starting methods such as DOL produce high inrush current and voltage sag, while soft-starter and inverter-based methods provide smoother torque transition and reduced starting current. Variation of stator resistance demonstrates a proportional effect on slip characteristics and torque, where higher resistance increases slip and reduces starting efficiency. In addition, starting methods may influence power quality parameters such as harmonic distortion, power factor, and voltage drop depending on the applied control strategy. The study concludes that integrating appropriate starting control with stator resistance adjustments can improve dynamic performance of induction motors and reduce power disturbances in industrial systems.